Emergency JJ Stent for Septic Shock under Remifentanil Sedation - An Option when Interventional Radiology is not available - Hannah Bykar; Gowrie Mohan S; Amit Patel; Ahilan Pathmanathan; Nikhil Vasdev (Archives of Clinical Nephrology - Peertechz Publications, 2015)
A 75-year-old man presented to the emergency department with a 2 day history of feeling generally unwell and with pain in his left renal angle. His past medical history included ischaemic heart disease, peripheral vascular disease with a previous AAA repair 6 years ago and 5 vessel CABG 3 years ago. He had prostate cancer with bone metastases and completed his 4th cycle of chemotherapy 3 days earlier. He was also in full remission for Non-Hodgkin's lymphoma since 2001. He was an ex-smoker, with a reduced exercise tolerance of 90 meters due to claudication, but independent in his activities of daily living.